(untitled) (KULT_online, 2019)
The Fictions of Translation gathers papers from the third Transfiction conference, which took place in Montreal in May 2015. As with the previous publications of the conference series, this volume aims to establish the concept of ‘transfiction’ as the basis of a new subdiscipline in translation studies. The 16 chapters of this collection explore a wide spectrum of ‘translation fictions’ that range from pseudo-translations, (non-)translator and (self-)translator biographies, to the discourse of translation institutions to show the potential of translation and ‘translation fictions’ in providing insights into past or contemporary social and political situations.